THE EFFECT OF TEAMS GAMES TOURNAMENT (TGT)STRATEGY WITH THE HELP OF WORD WALL APPLICATION ON THE STUDENTS’MASTERY OF SIMPLE PRESENT TENSE AT X GRADE OF SMA N 7 TANJUNGBALAI - Panjaitan, Agustina; Sari, Putri Lidiana Permata (UIN Sumatera Utara, 2023)
The goal of this research is to determine if the effect of Teams Games Tournament (TGT) Strategy With The Help of Word Wall Application on The Students’ Mastery of Simple Present Tense at X Grade of SMA N 7 Tanjungbalai. This research employed quantitative research with a two-class design, exprimental class and control class. This research's population consisted of all class X students from SMA Negeri 7 Tanjungbalai. Simple random sampling was used to choose two classes for the research sample: 32 students from the experimental class (X IPS 1) and 32 students from the control class (X IPS 2). A multiple choice test was used to collect data. The t-test formula was used to analyze the data. From this analysis, by comparing pre-test and post-test scores, the exprimental class had a lower pre-test mean score (53,4>56,6) and a higher post-test mean score (76,5>72,3) than the mean score in control class. This research found that using Teams Games Tournament (TGT) Strategy With The Help of Word Wall Application has significant effect in simple present tense. It can be proved by the result that tscore (to) = 11,25 was higher than the ttable (tt) = 1,999 with the significant 0,05 or it can be understood as To > Ttable (5% ) = 11,25>1,999. So, Ha is accepted. In another word, using Teams Games Tournament (TGT) Strategy With The Help of Word Wall Application more effective and more significant than using conventional way.